Healthy Eating: Lower Your Blood Pressure with DASH - Valerie Weyenberg; Karla P. Shelnutt; Linda B. Bobroff (EDIS)
FCS8884, a 2-page illustrated fact sheet by Valerie Weyenberg, Karla P. Shelnutt, and Linda B. Bobroff, outlines an eating plan rich in fruits, vegetables, and low-fat dairy products, that can prevent and reduce high blood pressure. Published by the UF Department of Family Youth and Community Sciences, October 2009.